The influence of the substrate-inclined angle on the section size of laser cladding layers based on robot with the inside-beam powder feeding. Issue 5 (February 2017) - Zhu, Gangxian; Shi, Shihong; Fu, Geyan; Shi, Jianjun; Yang, Shi; Meng, Weidong; Jiang, Fubing
Abstract Almost all of the application of laser cladding technology are based on horizontal reference plane at present, and this way has greatly limited its extensive application in non-horizontal reference plane. The substrate-inclined angles from 0° to 150° and continuously variable postures of coaxial powder nozzle have been achieved by changing the programming to control the laser processing robot adopting the technology of "hollow laser beam and internal powder feeding." The influence rules of the substrate-inclined angle on the section size of cladding layers were investigated, and the forces applied onto the molten pool were analyzed. The experimental results show that the section height of single track decreases, the section width of single track does not have significant variations, and the displacement offset between the axis by the peak point of cladding layer and the axis by center position of the molten pool is firstly increased and then decreased with the growth of the substrate-inclined angle. And the large-inclined angle of coaxial powder nozzle is applied and accomplished to clad on non-horizontal reference plane. A new process method is provided for laser cladding, repairing, and forming on non-horizontal reference plane by the inside-beam powder feeding technology.